1915 Armenian Van Revolt According To The Lev Nikolayevich Tolstoy’s (Famous Russian Author) Daughter Alexsandra Lvovna Tolstaya’s Memories - Şahin Doğan (Gazi Akademik Bakış)
In this article, it was evaluated the impressions and the information given about Armenian rebellion at Van according to the Alexsandra Lvovna Tolstaya’s Memories (Daughter of the famous Russian author Lev Nikolayevich Tolstoy) Where she came the last week of June in1915.